A feasibility study in establishing "Explore Philippines Tours" at Brgy. San Agustin Trece Martires City, Cavite - Sanoy, Neljoy R., author; Escover, Rozella A., author; Albao, Gerard P., author; Ventura, Elizabeth A., adviser (Rosario, Cavite : Cavite State University-CCAT Campus, 2010)
Thesis Abstract
A Feasibility Study (BSHRM)--Cavite State University-CCAT Campus, 2010.
Includes bibliographical references and appendices.
In English text.
Keywords: Tourism; Philippines; Tour guides; Employment; Travel and tours; Profitability